Contribution à l’étude des barrières et des leviers d’action face au changement climatique - Oumar Marega; Séverine Frere; Anne-Peggy Hellequin; Hervé Flanquart; Iratxe Calvo-Mendieta; Baptiste Berry; Sophie Cornet (VertigO)
The implementation of individual strategies to fight against climate change is a major issue both scientifically and environmentally as well as socially. This paper examines how people’s perceptions and territories characteristics could become barriers or drivers of action on climate change. The approach is based on a comparative study between Lille and Chauny, two towns climatically comparable, but differing from geographic and socio-economic factors. The findings show a diversity of perceptions and strategies to fight depending on two key determinants : geographic context and socio-economic variables. We demonstrate a diversity in climate change perceptions both related to people individual’s feeling, their educational level, and their main source of information. In terms of strategies to fight against climate change, our results reveal significant correlations between the measures adopted by people surveyed and their living standards. In our two study sites, most of the measures implemented are focused on climate change mitigation. Furthermore, people residing in Lille are more inclined to take mitigation actions than Chauny’s residents. One reason that could explain this difference between Lille and Chauny is the territorial and economic context.